Efektifitas Bimbingan Kelompok dengan Teknik Simulasi Untuk Meningkatkan Kemampuan Komunikasi Interpersonal Siswa Kelas X SMA Al-Rifa’ie Gondanglegi - Gaby Yohardini; Khairul Bariyyah; Romia Hari Susanti (JKI (Jurnal Konseling Indonesia), 2017)
Human life can not be separated from a communication, both verbal and non-verbal. Communication can take place in the context of interpersonal communication, interpersonal communication, group communication, organizational communication and also mass organization. Group counseling simulation technique is one way to reflect the realities of everyday life through the atmosphere to play and aims to help students learn about experiences related to social rules. The purpose of this study was to determine the effectiveness of group counseling with simulation techniques to improve interpersonal communication skills class X SMA Al-Rifa'ie Gondanglegi. The population of this research is class X MIA 1 and X IBB of 2 students and a sample of 10 students were taken by purposive sampling. Data were analyzed using SPSS 16.00 for windows by Wilcoxon Signed Ranks test . The results showed that the interpersonal communication skills of students before getting treatment pretest showed an average of 65 with a low category, and after getting treatment posttest showed an average of 109 with high category with the percentage increase in average by 68%. Based on test results obtained Wilcoxon Signed Ranks Test Z = - 2.807 with Asymp. Sig (2-tailed ) of 0.005 or less than 0.05. Which means that H0 is rejected and H1 is accepted it can be concluded that there are differences in interpersonal communication skills of students before getting treatment and after getting treatment simulation. This indicated that techniques to improve interpersonal communication skills class X SMA Al-Rifa'ie Gondanglegi.